2019
DOI: 10.3892/ijo.2019.4783
|View full text |Cite
|
Sign up to set email alerts
|

miR‑9 depletion suppresses the proliferation of osteosarcoma cells by targeting p16

Abstract: Osteosarcoma (OS) is a common primary malignancy in adolescents and children. MicroRNAs (miRNAs or miRs) can regulate the progression of OS. Herein, we explored the target genes and effects of miR-9 in OS. Cell growth, colony formation and cell cycle were respectively examined using a cell counting kit-8 (CCK-8), crystal violet staining and flow cytometry. The target gene of miR-9 was predicted according to the MicroRNA.org website. Luciferase activity was examined using a dual luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…[ 21 ] In osteosarcoma, inhibition of miR-9 decreases the proliferation of tumor cells by targeting p16. [ 39 , 40 ] In addition, miR-9 was upregulated in spontaneous canine osteosarcoma and promoted the invasion and migration of osteosarcoma cells. [ 41 ] Meanwhile, miR-9 was an oncogene and promoted proliferation of osteosarcoma through targeting Grap2 and cyclin D interacting protein.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] In osteosarcoma, inhibition of miR-9 decreases the proliferation of tumor cells by targeting p16. [ 39 , 40 ] In addition, miR-9 was upregulated in spontaneous canine osteosarcoma and promoted the invasion and migration of osteosarcoma cells. [ 41 ] Meanwhile, miR-9 was an oncogene and promoted proliferation of osteosarcoma through targeting Grap2 and cyclin D interacting protein.…”
Section: Discussionmentioning
confidence: 99%
“…The validated target genes include nuclear factor kappa B subunit 1 (NFKB1), chromodomain helicase DNA binding protein 1 (CHD1), www.bjbms.org VEGFA, vimentin (VIM), MMP13, and BCL2 interacting killer (BIK) [8]. In a recent study, Gao et al showed the p16 CDKN2A gene to be another target gene of miR-9 in OS [23].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, miR-9 depletion downregulated the extracellular signal-regulated kinase (ERK)/p38/c-Jun N-terminal kinase (JNK) pathway by targeting CDKN2A [23]. Abnormal cell cycle causes tumor growth and malignant cell proliferation [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with highly expressed levels of miR-9 in osteosarcoma tissues present bigger tumor size, more advanced clinical stages, more frequent distant metastasis, and lower survival rates [ 74 ]. The effect that miR-9 has on OS progression seems to be related to it targeting p16 and mediating the activation of the ERK/p38/JNK pathways [ 75 ]. Interestingly, the high expression of miR-9, occurs not only in OS tissues, but also in the serum of patients [ 76 ].…”
Section: Possible Applications Of Mirnas In Human Osteosarcomamentioning
confidence: 99%